KETERLIBATAN PEREMPUAN DALAM BIDANG POLITIK PADA MASA NABI MUHAMMAD SAW DAN MASA KHULAFAUR RASYIDIN (SUATU KAJIAN HISTORIS) - Marzuki Marzuki; Suharno Suharno (LPPM UNY, 2008)
The main problem in this research is how he figure of the women’s status in the reign period of Prophet Muhammad SAW and Kulafaur Rasyidin , how far is the involvement of women in the politic field in that period, and the problem which appeared at that period. This research is a descriptive qualitative research which is based on the library research. The data of research contains the information about the involvement of women in the politic field in the reign period of Prophet Muhamamad Saw and Khulafaur Rasyidin which are collected from the Islamic literature such as hadists of Prophet Muhammad Saw and the historical books of Islam which reveal the problems. The collected data is analyzed qualitatively with the inductive analysis techniques. The research has shown that the condition of women in the middle of pagan ignorance age proceeding the Islamic era (Jahiliyah) of Arabic Society commonly was terrified. The women were insulted, treated harshly, and looked down. Moreover, the women were seen as the realization of sin, unfortunate, disgrace and the other embarrass things. Islam has put the status of women in the proportion by admitting the women’s humanity and getting rid of the darkness which has been experienced by the women in the life time history. During the reign period of Prophet Muhammad Saw, the women had already taken part in the politic role such as in the struggle of spreading the truth of Allah’s sentences. They had done the Islamic religious proselytizing, hijrah with the prophet Muhammad Saw, and swore to the Prophet Muhammad Saw as well done the jihad or taken a part in the war which used to be followed by the men. The women also had activated in taking part in the role of politic in the period of Khulafaur Rasyidin. Ummahat al-Mu’minin had become the motored movement of women to participate actively in those politic activities. Among the problems which faced by the women in participating in the politic field during the reign of Prophet Muhammad Saw were the pressure of infidel Quraisy groups of Makkah in the early period of Islamic religious proselytizing, the physical weaknesses of women considering the hard activities which were done to hijrah and holy war (jihad). For example they had to lose their family, wealthy and motherhood. However, those kinds of problems didn’t stop the role of women’s in the politic field. The big problem which was faced in the period of Khulafaur Rasyidin was the disputed that encountered in the riot time was among the Moslem and also the unbeliever who pretended to be Moslem (munafik) such as the one which was motorized by Abdullah bin Saba.